Preparation method of vanadium-titanium pellets

By mixing siderite fine grinding with vanadium titanium concentrate to make spheres and performing specific heat treatment, the problems of uneven oxidation of vanadium titanium pellets and low utilization efficiency of cheap siderite resources are solved, and the resistance of pellets is improved The compressive strength and reduce production costs, achieving efficient preparation of vanadium titanium pelletized ore.

CN119220811AActive Publication Date: 2024-12-31PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411457711.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-31
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing vanadium titanium pellet ore has uneven oxidation effect during the preheating process, resulting in a decrease in compressive strength and low efficiency in using cheap siderite resources, which increases production costs.

Method used

By sieving and grinding siderite, finely grinding, and mixing it with vanadium titanium concentrate and bentonite, it is dried, preheated and calcined to form a good pore channel, which improves the compressive strength of the pellet ore and is effectively used. Utilize cheap siderite resources.

Benefits of technology

It realizes uniform oxidation of vanadium titanium pellet ore during preheating and roasting, improves compressive strength, reduces production costs, simplifies processes and equipment, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

A preparation method of vanadium-titanium pellets comprises the following steps: a) siderite is screened and classified, and the part smaller than 6 mm is subjected to fine grinding treatment, so that the siderite subjected to fine grinding is obtained; b) mixing the finely ground siderite obtained in the step a) with vanadium-titanium concentrate and bentonite, and pelletizing to obtain green pellets with the pellet fraction of 8-16mm; and c) distributing the green pellets with the pellet fraction of 8-16 mm obtained in the step b), drying, preheating, roasting and cooling in sequence to obtain the vanadium-titanium pellets. Compared with the prior art, the preparation method of the vanadium-titanium pellets provided by the invention has the advantages that siderite is introduced as a raw material for graded preparation, and overall better interaction is realized through specific process steps and conditions, so that a good pore channel can be formed during preheating and roasting of the pellets produced by fine-fraction high-titanium vanadium-titanium magnetite; uniform oxidation in the preheating and roasting process is guaranteed, the compressive strength of the pellets is improved, cheap siderite resources can be effectively utilized, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steel smelting, and more specifically to a method for preparing vanadium-titanium pellets. Background Art

[0002] How to improve the comprehensive utilization efficiency of vanadium-titanium magnetite has long been a technical problem that technicians in the field need to solve. At the same time, researchers in the industry have also been committed to improving the TFe grade of iron ore concentrate to reduce ironmaking costs. In the past decade, due to the limitations of ore properties and equipment, the TFe grade of Midea iron ore concentrate has been maintained at 53.5%, and the TFe grade of Baima iron ore concentrate has been maintained at 55%~56%, which is much lower than the TFe grade of ordinary iron ore concentrate (63%~67%). To this end, technical personnel in this field have carried out research on mineral processing technology, and the TFe grade of Midi vanadium-titanium concentrate has been increased to 55.5%, and the TFe grade of Baima vanadium-titanium concentrate has been increased to more than 57%; but with the increase of TFe grade, the particle size of the vanadium-titanium concentrate is greatly refined, and the refined vanadium-titanium concentrate enters the pellet. During the preheating process, the Fe3O4 on the outside of the pellet is rapidly oxidized to form a relatively dense Fe2O3 oxide shell, which hinders the entry of oxygen into the interior of the pellet, resulting in poor preheating oxidation effect. The Fe3O4 inside the pellet can only be fully oxidized in the roasting stage, which leads to uneven oxidation time and degree of oxidation, forming a concentric crack structure, which greatly reduces the compressive strength of the vanadium-titanium pellet.

[0003] Iron in siderite mainly exists in the form of FeCO3. Theoretically, siderite begins to decompose at about 400℃ and completely decomposes at 560℃. The general preheating temperature of pellets is about 800℃. Under high temperature conditions, FeCO3 completely decomposes to produce FeO and CO2, and tends to form stable Fe3O4 or Fe2O3 under sintering conditions. Due to this characteristic, its addition to sintering affects the strength of sintered ore, so many steel companies are reluctant to use it. However, with the continuous production of steel companies, iron ore resources are becoming less and less, and the cost of ore mining is getting higher and higher, resulting in a substantial increase in the cost of pig iron. For this reason, the use of low-priced siderite has become an important technical measure for various steel companies to reduce production costs. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a method for preparing vanadium-titanium pellets, which uses siderite as raw material and carries out graded preparation. It can not only form good pore channels for the pellets produced from fine-grained high-titanium vanadium-titanium magnetite during preheating and roasting, ensure uniform oxidation during preheating and roasting, and improve the compressive strength of the pellets, but also effectively utilize cheap siderite resources and reduce production costs.

[0005] The present invention provides a method for preparing vanadium-titanium pellets, comprising the following steps:

[0006] a) After the siderite is screened and classified, the part smaller than 6 mm is finely ground to obtain finely ground siderite;

[0007] b) mixing the finely ground siderite obtained in step a) with vanadium-titanium concentrate and bentonite, and pelletizing to obtain green balls with a pellet size of 8 to 16 mm;

[0008] c) The green balls with a pellet size of 8 to 16 mm obtained in step b) are distributed, dried, preheated and roasted in sequence, and cooled to obtain vanadium-titanium pellets.

[0009] Preferably, the screening and grading in step a) respectively obtains a portion greater than or equal to 6 mm and a portion less than 6 mm; wherein the portion greater than or equal to 6 mm is used for the distribution process in step c).

[0010] Preferably, the requirement for the fine grinding treatment in step a) is that the fine grinding to a particle size less than 0.074 mm accounts for 70%.

[0011] Preferably, the mass ratio of the finely ground siderite to the vanadium-titanium concentrate and bentonite in step b) is (4-14):1:(35-45).

[0012] Preferably, the pelletizing process in step b) is specifically as follows:

[0013] The mixed materials are added into a disc pelletizing machine for pelletizing, and the moisture content is controlled at 7.5%-8.5% to obtain raw pellets with a pellet size of 8-16 mm.

[0014] Preferably, the disc pelletizing machine has a specification of Φ (6000-8000) mm × (900-1100) mm, a rotation speed of 10 r / min-30 r / min, and an inclination angle of 45°-50°.

[0015] Preferably, the process of making the cloth in step c) is specifically as follows:

[0016] The siderite sieved and graded greater than or equal to 6 mm in step a) is evenly distributed on the belt roasting machine trolley to form a base material, and the number of layers is controlled to be 2 to 3. After the base material is laid, the green balls with a pellet size of 8 to 16 mm obtained in step b) are evenly distributed on the base material layer by layer, and at the same time, the siderite edge materials greater than or equal to 6 mm are laid on both sides of the green balls to complete the laying process.

[0017] Preferably, the drying temperature in step c) is 280° C. to 320° C., and the drying time is 20 min to 40 min.

[0018] Preferably, the preheating temperature in step c) is 750° C. to 850° C., and the preheating time is 5 min to 15 min.

[0019] Preferably, the calcination temperature in step c) is 1200° C. to 1300° C., and the calcination time is 10 min to 20 min.

[0020] The present invention provides a method for preparing vanadium-titanium pellets, comprising the following steps: a) after screening and grading siderite, fine grinding the part smaller than 6 mm to obtain finely ground siderite; b) mixing the finely ground siderite obtained in step a) with vanadium-titanium concentrate and bentonite, and then pelletizing to obtain green balls with a pellet size of 8 to 16 mm; c) distributing the green balls with a pellet size of 8 to 16 mm obtained in step b), drying, preheating and roasting in sequence, and cooling to obtain vanadium-titanium pellets. Compared with the prior art, the method for preparing vanadium-titanium pellets provided by the present invention introduces siderite as a raw material for graded preparation, and achieves overall good interaction through specific process steps and conditions, which can not only form good pore channels for the pellets produced by fine-grained high-titanium vanadium-titanium magnetite during preheating and roasting, ensure uniform oxidation during preheating and roasting, and improve the compressive strength of the pellets, but also effectively utilize cheap siderite resources and reduce production costs.

[0021] At the same time, the preparation method of the vanadium-titanium pellet ore provided by the present invention has simple process, concise equipment, easy operation, significant effect, and broad application prospects. DETAILED DESCRIPTION

[0022] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The present invention provides a method for preparing vanadium-titanium pellets, comprising the following steps:

[0024] a) After the siderite is screened and classified, the part smaller than 6 mm is finely ground to obtain finely ground siderite;

[0025] b) mixing the finely ground siderite obtained in step a) with vanadium-titanium concentrate and bentonite, and pelletizing to obtain green balls with a pellet size of 8 to 16 mm;

[0026] c) The green balls with a pellet size of 8 to 16 mm obtained in step b) are distributed, dried, preheated and roasted in sequence, and cooled to obtain vanadium-titanium pellets.

[0027] The present invention is mainly aimed at a utilization method proposed for the siderite resources around the Panxi area, which can not only well drive the exploitation of the surrounding siderite resources, but also improve the quality index of ultra-fine-grained vanadium-titanium concentrate pellets through novel technical means, while increasing the pellet output, reducing the consumption of the bottom and side materials for pellets, and creating economic benefits. The present invention first screens and grades the siderite, and then distributes the large siderite particles of 6 mm or more as the bottom and side materials for belt pellet roasting, and puts the small siderite particles of less than 6 mm into a tower mill for fine grinding, and then uses them to produce vanadium-titanium pellet raw balls, and then evenly distributes the vanadium-titanium pellet raw balls on the belt roaster for pellet roasting, and recycles the decomposed and crushed bottom and side siderite. The preparation method provided by the present invention can effectively utilize siderite resources, recover a large amount of iron elements in ore resources, and its mining cost is relatively low, which can reduce the cost of pig iron manufacturing and create economic benefits; at the same time, it can drive the mining of surrounding siderite resources, provide jobs for surrounding people, and have obvious social benefits.

[0028] The present invention first screens and grades the siderite, and then finely grinds the part smaller than 6 mm to obtain finely ground siderite. In the present invention, the siderite is a resource mined from surrounding mines, and its chemical composition index is preferably:

[0029] w (TFe) 30% ~ 35%, w (SiO2) 15% ~ 18%, w (Al2O3) < 2.5%, w (CaO) < 3%, w (burning loss) 22% ~ 25%.

[0030] At present, the mining of siderite resources is relatively small, and it belongs to off-balance sheet mining. The weight percentage of coarse and fine particles is not much different. It needs to be screened and graded before pellet preparation and distribution. The screening and grading is preferably carried out according to two particle sizes, and the part greater than or equal to 6 mm (set according to the grate width of the belt roaster) and the part less than 6 mm are obtained respectively; among which, the part less than 6 mm is finely ground, and the part greater than or equal to 6 mm is used for the distribution process in step c) for bottom and edge laying.

[0031] In the present invention, the requirement for the fine grinding treatment is preferably: the fine grinding to a particle size less than 0.074 mm accounts for 70%; the fine grinding treatment is carried out using a tower mill well known to those skilled in the art, and the present invention has no special restrictions on this.

[0032] After obtaining the finely ground siderite, the present invention mixes the obtained finely ground siderite with vanadium-titanium concentrate and bentonite, and then performs ball making to obtain green balls with a pellet size of 8 to 16 mm. In the present invention, the vanadium-titanium concentrate is preferably Baima concentrate, which belongs to the ultrafine-grade high-titanium vanadium-titanium magnetite concentrate; the vanadium-titanium magnetite concentrate with a particle size of less than 0.074 mm accounts for about 95%, and the ball forming index is about 0.5.

[0033] In the present invention, the bentonite serves as a binder. The present invention has no special limitation on its source, and commercially available products known to those skilled in the art may be used. The proportion of the bentonite particles smaller than 0.074 mm is about 99%.

[0034] The pelletizing material of the present invention adopts the structural form of "vanadium-titanium concentrate + siderite + bentonite". Through pelletizing experimental research, it is found that after roasting, the compressive strength of the pelletized ore is significantly increased.

[0035] In the present invention, the mass ratio of the finely ground siderite to the vanadium-titanium concentrate and bentonite is preferably (4-14):1:(35-45).

[0036] The present invention has no special limitation on the mixing process, and a V-shaped mixer well known to those skilled in the art can be used to uniformly mix for 5 minutes to 15 minutes.

[0037] In the present invention, the process of pelletizing is preferably as follows:

[0038] The mixed materials are added into a disc pelletizing machine for pelletizing, and the moisture content is controlled at 7.5%-8.5% to obtain raw pellets with a pellet size of 8-16 mm.

[0039] In the present invention, the mixed material added to the disc pelletizing machine is first prepared into mother balls of about 1 mm by a water dripping mode, and then replaced with mist water to continue making balls, and the mixed material is evenly wrapped around the mother ball by spraying mist water while adding the mixed material, and the raw ball particle size is ensured to reach 8-16 mm, forming vanadium-titanium raw balls, and the moisture content is controlled at 8.0%±0.5%.

[0040] In the present invention, the specification of the disc pelletizing machine is preferably Φ (6000~8000) mm×(900~1100) mm, the rotation speed is preferably 10r / min~30r / min, more preferably 20r / min~25r / min, and the inclination angle is preferably 45°~50° (adjustable).

[0041] In the present invention, the particle size of the green balls obtained by ball making is preferably 8-16 mm, and the falling strength of the green balls is controlled to be greater than 4 times / ball (0.5 m), and the compressive strength is controlled to be greater than 10 N / ball.

[0042] After obtaining green balls with a pellet size of 8 to 16 mm, the present invention distributes the green balls with a pellet size of 8 to 16 mm, and then sequentially dries, preheats and roasts them, and then cools them to obtain vanadium-titanium pellets.

[0043] In the present invention, the process of the cloth is preferably as follows:

[0044] The siderite sieved and graded greater than or equal to 6 mm in step a) is evenly distributed on the belt roasting machine trolley to form a base material, and the number of layers is controlled to be 2-3. After the base material is laid, the green balls with a particle size of 8-16 mm obtained in step b) are evenly distributed on the base material layer by layer, and at the same time, siderite edge materials greater than or equal to 6 mm are laid on both sides of the green balls to ensure that the bottom and side walls of the belt roasting machine trolley will not be damaged due to the excessively high roasting temperature, thereby completing the material laying process.

[0045] In the present invention, the drying temperature is preferably 280° C. to 320° C., and the drying time is preferably 20 min to 40 min.

[0046] In the present invention, the preheating temperature is preferably 750°C to 850°C, more preferably 800°C to 850°C, and the preheating time is preferably 5 min to 15 min, more preferably 10 min to 12 min.

[0047] In the present invention, the calcination temperature is preferably 1200° C. to 1300° C., more preferably 1250° C., and the calcination time is preferably 10 min to 20 min, more preferably 15 min.

[0048] In the present invention, after the roasting is completed, the pellets are taken out and placed in a natural environment with good ventilation for cooling; finally, the compressive strength of the cooled pellets is tested.

[0049] In the present invention, the particle size of the vanadium-titanium pellets obtained by the preparation method is 8-16 mm, and the compressive strength is greater than 2200N.

[0050] The present invention provides a method for preparing vanadium-titanium pellets, which has the following beneficial effects:

[0051] (1) Using large-sized siderite to replace finished pellets as bottom and side materials can reduce the amount of recycled roasting of finished pellets, greatly save the gas consumption of the pelletizing process, and reduce production costs; (2) Taking advantage of the characteristic of siderite that it begins to decompose at 400°C, it forms CO2 pore channels during the preheating process of vanadium-titanium pellets, improves the formation of dense Fe2O3 oxide layer of ultra-fine-grained vanadium-titanium concentrate, promotes the uniformity of oxidation inside and outside the pellets, improves the occurrence of concentric cracks, and improves the compressive strength of vanadium-titanium pellets; (3) The cheap and low-grade siderite resources in the surrounding areas of Panxi are recycled and utilized, which drives the mining of surrounding siderite resources, provides jobs for the surrounding people, and has obvious social benefits.

[0052] The present invention provides a method for preparing vanadium-titanium pellets, comprising the following steps: a) after screening and grading siderite, fine grinding the part smaller than 6 mm to obtain finely ground siderite; b) mixing the finely ground siderite obtained in step a) with vanadium-titanium concentrate and bentonite, and then pelletizing to obtain green balls with a pellet size of 8 to 16 mm; c) distributing the green balls with a pellet size of 8 to 16 mm obtained in step b), drying, preheating and roasting in sequence, and cooling to obtain vanadium-titanium pellets. Compared with the prior art, the method for preparing vanadium-titanium pellets provided by the present invention introduces siderite as a raw material for graded preparation, and achieves overall good interaction through specific process steps and conditions, which can not only form good pore channels for the pellets produced by fine-grained high-titanium vanadium-titanium magnetite during preheating and roasting, ensure uniform oxidation during preheating and roasting, and improve the compressive strength of the pellets, but also effectively utilize cheap siderite resources and reduce production costs.

[0053] At the same time, the preparation method of the vanadium-titanium pellet ore provided by the present invention has simple process, concise equipment, easy operation, significant effect, and broad application prospects.

[0054] In order to further illustrate the present invention, the following examples are used to provide a detailed description. The physical and chemical parameters of the ultrafine vanadium-titanium concentrate, bentonite and finely ground siderite used in the following examples of the present invention are shown in Table 1 below.

[0055] Table 1 Particle size distribution of the materials used (particle size composition, unit: wt%)

[0056]

[0057] The chemical composition indicators of the materials used in Table 1 are as follows:

[0058] Vanadium-titanium concentrate: w(TFe) 55.00%~56.50%, w(FeO)>29%, w(SiO2) 3.30%~3.50%, w(TiO2) 11.00%~11.50%, w(V2O5) 0.60%~0.65%;

[0059] Bentonite: w(CaO)2.00%~5.00%, w(SiO2)40.00%~60.00%, w(Al2O3)12.00%~18%, w(MgO)2.00%~5.00%;

[0060] Siderite: w(TFe) 30%~35%, w(SiO2) 15%~18%, w(Al2O3)<2.5%, w(CaO)<3%, w(burn loss) 22%~25%.

[0061] The raw material ratio of vanadium-titanium pellets is shown in Table 2 below.

[0062] Table 2 Raw material ratio (wt%)

[0063]

[0064] The specific preparation process is as follows:

[0065] First, the massive siderite concentrate is screened and graded into a part greater than or equal to 6 mm and a part less than 6 mm, wherein the part less than 6 mm is finely ground until the particle size is less than 0.074 mm, accounting for about 70%; then, according to the ratio shown in Table 2, the corresponding weight percentage of vanadium-titanium concentrate, bentonite and finely ground siderite are weighed, and put into a drying drum for drying, and the moisture content after drying is controlled to 7.0%±0.5%, and then the dried mixture is put into a strong mixer for sufficient mixing, and the mixing time is 10 minutes; the mixed mixture is added to a disc pelletizer for pelletizing, and the moisture content is controlled to 7.5%~8.5%. The disc pelletizer is Φ7000×1000mm, with a rotation speed of 20r / min and an inclination of 48°, and a qualified raw ball with a pellet size of 8~16mm is produced.

[0066] The drop strength and compressive strength of the green balls are tested; the drop strength test method is: raise the green balls to a height of 0.5M, and then let them fall freely onto an iron plate, and count the number of times the green balls break as the number of drops; the compressive strength test method is: directly place the green balls into the compression equipment for testing.

[0067] Finally, the screened siderite with a size greater than or equal to 6 mm is evenly distributed on the belt roasting machine trolley to form a base material, and the number of layers is controlled to be 2 to 3. After the base material is laid, the prepared qualified green balls are evenly laid on the base material layer by layer, and at the same time, siderite edge materials with a size greater than or equal to 6 mm are laid on both sides of the green balls to ensure that the bottom and side walls of the belt roasting machine trolley will not be damaged due to the high roasting temperature; finally, the qualified green balls after laying are dried, preheated and roasted, and the drying, preheating and roasting system is: drying temperature 300°C, drying time 30min, preheating temperature 800°C, preheating time 10min, roasting temperature 1250°C, roasting time 15min, and after roasting is completed, they are taken out and naturally cooled to obtain vanadium-titanium pellets; finally, the compressive strength of the cooled vanadium-titanium pellets is tested.

[0068] The following specifically provides various comparative indicators of the raw balls and finished balls of Comparative Example 1 and Examples 1 to 4.

[0069] Comparative Example 1

[0070] The vanadium-titanium iron concentrate is added with 98% and bentonite with 2%. The compressive strength of the green balls is 10.68N / piece, the drop strength is 4.7 times / piece, the moisture content of the green balls is 8.04%, and the burst temperature is greater than 600℃; the compressive strength of the finished balls is 1934N / piece, the internal porosity is 18.51%, the reduction degree of the pellets is 65.24%, the hematite phase composition reaches 92.76%, and the belt roaster utilization factor is 0.88t / (m 2 h).

[0071] Example 1

[0072] The vanadium-titanium iron concentrate is added with 90%, bentonite with 2%, and finely ground siderite with 8%. The compressive strength of the green balls is 10.47N / piece, the drop strength is 4.6 times / piece, the moisture content of the green balls is 7.87%, and the burst temperature is greater than 600℃; the compressive strength of the finished balls is 2214N / piece, the internal porosity is 25.42%, the reduction degree of the pellets is 68.16%, the hematite phase composition reaches 93.65%, and the belt roaster utilization factor is 0.89t / (m 2 h).

[0073] Example 2

[0074] The vanadium-titanium iron concentrate is added with 80%, bentonite with 2%, and finely ground siderite with 18%. The compressive strength of the green balls is 10.07N / piece, the drop strength is 4.5 times / piece, the moisture content of the green balls is 7.78%, and the burst temperature is greater than 600℃; the compressive strength of the finished balls is 2460N / piece, the internal porosity is 34.79%, the reduction degree of the pellets is 70.06%, the hematite phase composition reaches 94.59%, and the belt roaster utilization factor is 0.90t / (m 2 h).

[0075] Example 3

[0076] The vanadium-titanium iron concentrate is added with 70%, bentonite with 2%, and finely ground siderite with 28%. The compressive strength of the green balls is 9.56N / piece, the drop strength is 4.2 times / piece, the moisture content of the green balls is 7.92%, and the burst temperature is greater than 600℃; the compressive strength of the finished balls is 2160N / piece, the internal porosity is 39.44%, the reduction degree of the pellets is 72.17%, the hematite phase composition reaches 95.67%, and the belt roaster utilization factor is 0.92t / (m 2 h).

[0077] The experimental results show that with the further increase of the siderite ratio, the falling strength and compressive strength of the green balls show a certain decline in quality, especially the compressive strength is less than 10N, which gradually fails to meet the production requirements; the reduction degree of the pellets is gradually optimized, and the quality of the vanadium-titanium pellets produced by the ultra-fine vanadium-titanium concentrate is significantly improved. The large-particle siderite replaces the bottom and side material pellets, the pellet output increases, and the belt roaster utilization coefficient increases from 0.88t / (m 2 h) was increased to 0.92t / (m 2 ·h), the production efficiency is significantly improved; however, as the siderite ratio is gradually increased, the compressive strength of the finished pellets first increases and then decreases, and the highest is 2460N in Example 2. When the siderite ratio is further increased, the compressive strength decreases to 2160N. The main reason is that the roasting decomposition effect increases, the porosity is too developed, and the compressive strength is reduced. Therefore, the optimal range of siderite is 18%±5%.

[0078] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing vanadium-titanium pellets, comprising the following steps: a) After the siderite is screened and classified, the part smaller than 6 mm is finely ground to obtain finely ground siderite; b) mixing the finely ground siderite obtained in step a) with vanadium-titanium concentrate and bentonite, and pelletizing to obtain green balls with a pellet size of 8 to 16 mm; c) The green balls with a pellet size of 8 to 16 mm obtained in step b) are distributed, dried, preheated and roasted in sequence, and cooled to obtain vanadium-titanium pellets.

2. The method for preparing vanadium-titanium pellets according to claim 1, characterized in that: The screening and grading in step a) respectively obtains a portion greater than or equal to 6 mm and a portion less than 6 mm; wherein the portion greater than or equal to 6 mm is used for the material distribution process in step c).

3. The method for preparing vanadium-titanium pellets according to claim 1, characterized in that: The requirement for the fine grinding process in step a) is that the fine grinding to a particle size less than 0.074 mm accounts for 70%.

4. The method for preparing vanadium-titanium pellets according to claim 1, characterized in that: The mass ratio of the finely ground siderite to the vanadium-titanium concentrate and bentonite in step b) is (4-14):1:(35-45).

5. The method for preparing vanadium-titanium pellets according to claim 1, characterized in that: The process of pelletizing in step b) is specifically as follows: The mixed materials are added into a disc pelletizing machine for pelletizing, and the moisture content is controlled at 7.5%-8.5% to obtain raw pellets with a pellet size of 8-16 mm.

6. The method for preparing vanadium-titanium pellets according to claim 5, characterized in that: The specification of the disc pelletizing machine is Φ (6000-8000) mm×(900-1100) mm, the rotation speed is 10 r / min-30 r / min, and the inclination angle is 45°-50°.

7. The method for preparing vanadium-titanium pellets according to claim 1, characterized in that: The process of the cloth in step c) is specifically as follows: The siderite sieved and graded greater than or equal to 6 mm in step a) is evenly distributed on the belt roasting machine trolley to form a base material, and the number of layers is controlled to be 2 to 3. After the base material is laid, the green balls with a pellet size of 8 to 16 mm obtained in step b) are evenly distributed on the base material layer by layer, and at the same time, the siderite edge materials greater than or equal to 6 mm are laid on both sides of the green balls to complete the laying process.

8. The method for preparing vanadium-titanium pellets according to claim 1, characterized in that: The drying temperature in step c) is 280° C. to 320° C., and the drying time is 20 min to 40 min.

9. The method for preparing vanadium-titanium pellets according to claim 1, characterized in that: The preheating temperature in step c) is 750° C. to 850° C., and the preheating time is 5 min to 15 min.

10. The method for preparing vanadium-titanium pellets according to claim 1, characterized in that: The calcination temperature in step c) is 1200° C. to 1300° C., and the calcination time is 10 min to 20 min.

Citation Information

Patent Citations

  • Method for increasing yield of sintering ore by utilizing siderite

    CN103834799A

  • Sintering method of siderite by graded distribution

    CN108425008A

  • Process method for processing pellet ores by using siderite powder and vanadium-titanium magnetite powder

    CN108998659A

  • Charge for producing fluxed pellets

    SU855037A1